The Influence of Audio-Visual Media On the Ability to Understand Up Space Students - Umaru Zubairu (CV. AFDIFAL MAJU BERKAH, 2021)
The purpose of this research is to determine the effect of audio-visual media in the understanding of wake space , to know the results of student learning in the field of study of mathematics as well as determine whether there is a significant influence between the influence of teaching using audio visual media on student learning outcomes in the field of study of Mathematics. The research instrument used was a test writing essay form test as much as 5 grains of matter to the pretest and 5 grains of matter to posttest. As the population in this research is all which amounted to 28 people and the sample in this research is all students as Respondents. From the analysis of the data obtained some findings that average To the average value of the pretest experiments (67,79) and the average pretest before using the conventional method (51). while in post-test data after teaching using audio visual media for the average value of posttest (80.50) and the average value of teaching using conventional methods on the posttest is (76,11). From the calculation between the t with ttable if – t1 – ½ < t < t1 – 1/2< , where -1,217 < 2,24 < 1,217 then Based on this case, H0 is rejected while the Ha accepted which stated “There is a significant effect between teaching using audio visual media on the ability to understand up the space of students.